Legal Analysis of the Political Policy on the Free Nutritious Meal (MBG) Program of the Prabowo–Gibran Administration Lacking a Legal Framework - Oktoriusman Halawa (CV. Publikasi Indonesia, 2026)
This legal research aims to examine the legal certainty of the implementation of the Free Nutritious Meal Program (MBG) by the Prabowo-Gibran government to achieve legal certainty and good governance. This study employs a normative juridical approach, using primary data derived from laws, regulations, and court decisions. The results indicate that the implementation of the MBG program by the Prabowo-Gibran government lacks a clear and definitive legal basis, which is not aligned with the objectives of the law and the principles of good governance. The conclusion of this study emphasizes that the implementation of the MBG program by the Prabowo-Gibran administration lacks a strong and well-defined legal framework, resulting in inconsistency with the objectives of the law and the principles of good governance. Therefore, it is recommended that the government promptly evaluate and strengthen the legal foundation of the MBG program, preferably through a Government Regulation or, ideally, through a Law, to ensure legal certainty and the realization of good governance.